Gyneco-obstetric complications in acute bartonellosis: 50 cases observed in Caraz, Ancash - López Guimaraes, Douglas (2024)
Objective: to evaluate obstetric complications arising in pregnant native women with acute bartonellosis due to Bartonella bacilliformis in an endemic area in Caraz, Ancash, at 2 237 m above sea level. Material and method: 50 pregnant women were enrolled consecutively in San Juan de Dios Hospital, Caraz, between 1999 and 2003. All cases had the diagnosis of bartonellosis, based on a Bartonella-positive peripheral blood smear.  Results: all pregnant women were native and living in the endemic area; 64% came from adjacent rural areas, 12% had an antecedent of "verruga peruana" and 10 % had previously received treatment for "verruga". The features of early acute bartonellosis (Carrión's disease) in these patients were paleness (80%), headache (76 %), articular pain (64%), fever (34 %), abdominal pain (24 %) and vaginal bleeding (18%). The average age was 25,5 years. The average gestational age when seen was 22,9 weeks. The average hemoglobin was 9,8 g/dL. The average parasitic index (proportion of parasitized red cells) was 23,2%, range 1-100; only 22 % had a high parasitic index, over 50 % in their blood smears. 48% of patients had obstetric complications: abortions 26%, premature labor 8%, fetal death 4 %, placental retention 4 % and sepsis 2%. The obstetric complications were more frequent during the first trimester of pregnancy with 71,4 %. There were no maternal deaths in this cohort.  Conclusion: in endemic areas, pregnant women suffering from Carrión's disease (acute bartonellosis by B. bacilliformis) had a high frequency of obstetric complications; the disease poses a high risk to pregnant women.